The economics of public issues - Miller, Roger LeRoy (Addison Wesley, 2001)
The twelfth edition continues the tradition of illustrating traditional economic principles through contemporary issues by offering eight all-new chapters on compelling topics such as the economics of traffic jams, slave redemption in Sudan, and the Microsoft monopoly. The authors' clear presentation and straightforward applications make the study of economics entertaining and informative. The Economics of Public Issues is an essential source of engaging, relevant readings for a principles of economics course, and an excellent way to spark independent thinking in political economy, public policy, and social issues courses.